2014
DOI: 10.1186/2052-8426-2-20
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of how HIV kills infected CD4 T cells: implications for HIV cure

Abstract: Defining how HIV does, and does not, kill the host CD4 T cell that it infects is of paramount importance in an era when research is approaching a cure for infection. Three mutually exclusive pathways can lead to the death of HIV-infected cells during the HIV life cycle, before, coincident and after HIV integration and consequently may affect viral replication. We discuss the molecular mechanism underlying these pathways, the evidence supporting their roles in vivo, and contemplate how understanding these pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 59 publications
1
26
0
2
Order By: Relevance
“…systemic inflammation, potentially reducing future HIVrelated complications (such as cardiovascular events) triggered by BT and inflammation. In this context, several studies have previously demonstrated that starting treatment with INSTIs and/or the intensification or switching to this regimen is associated with a favourable effect on HIVrelated immune activation and also with inhibition of CD4-T cell depletion [28][29][30][31][32] which is in line with our findings. It is also important to note than although an increase in BT and inflammation was observed in HIV-infected patients compared with the controls, such a difference was only significant in HIV-patients using cART.…”
Section: Discussionsupporting
confidence: 92%
“…systemic inflammation, potentially reducing future HIVrelated complications (such as cardiovascular events) triggered by BT and inflammation. In this context, several studies have previously demonstrated that starting treatment with INSTIs and/or the intensification or switching to this regimen is associated with a favourable effect on HIVrelated immune activation and also with inhibition of CD4-T cell depletion [28][29][30][31][32] which is in line with our findings. It is also important to note than although an increase in BT and inflammation was observed in HIV-infected patients compared with the controls, such a difference was only significant in HIV-patients using cART.…”
Section: Discussionsupporting
confidence: 92%
“…This gene is analogous to the pol gene that encodes reverse transcriptase (RT) and integrase. The integration of the viral genome into the host cell's DNA has a high probability of failing, which is referred to as abortive infection, often leading to apoptosis or pyroptosis of the cell [20]. We model this with a virus-controlled parameter f , representing the fraction of successfully infected cells.…”
Section: The Most Obvious Parameter Under Control Of the Virus Is Thementioning
confidence: 99%
“…Variation in d V can further be caused by differences in antibody affinities and concentrations. Even in the absence of an immune response, an infected cell experiences a virus-induced cytopathic effect [20]. We model this using a viruscontrolled parameter α, which is added to the death rate of virion producing cells.…”
Section: The Most Obvious Parameter Under Control Of the Virus Is Thementioning
confidence: 99%
“…While many strategies promote the elimination of virus-expressing cells via the immune system (8)(9)(10)(11), another approach is to directly target and kill latent HIV-infected T cells (12). There is evidence that HIV infection affects both pro-apoptotic and anti-apoptotic signaling pathways (13)(14)(15) and targeting these pathways in combination with LRAs has the potential to reduce reservoir size (16). However, due to the interconnected, multivariate nature of signaling pathways that regulate apoptosis (17)(18)(19) and the heterogeneous nature of latent HIV activation (20,21), successful identification of novel therapeutic targets requires systems-level single-cell analysis.…”
Section: Introductionmentioning
confidence: 99%